CHEMISTRY OF MICROLITES AND DAUGHTER MINERALS IN MELT INCLUSIONS IN THE CONTEXT OF GENETIC PROBLEMS: AN EXAMPLE OF THE MALOMURUNSKII MASSIF - Panina L.I.; Usol'tseva L.M.; Pospelova L.N. (My University, 2003)
The morphology and chemistry of small grains (microlites and daughter phases in melt inclusions) of 20 minerals were examined in rocks from the Malomurunskii Massif. Along with minerals previously known in the massif, the micrograins were determined to contain newly found phases: clintonite, larnite, magnesioferrite, hauyne, a Th-U silicate, and Ba- and Sr-rich varieties of ekanite. The results obtained on the micrograins allowed us to trace in much detail the compositional trends of minerals starting from the very early stages of their crystallization up to the closing stages of this process and to consider the behavior of some elements in the magmatic process from the genetic viewpoint. It was determined that the composition of microlites and daughter phases in inclusions in minerals from earlier rocks do not contradict concepts that the rock complex was produced from a parental alkaline basaltic magma. The regularities in the variations in the Mg# of the mafic minerals point to the action of crystallization differentiation. It was determined that Al in the pyroxene, melilite, and phlogopite behaves unsystematically (significant variations in the Al concentrations from high to low values and a subsequent increase to high values), which can be explained within the framework of the previously proposed hypothesis that the high-Al alkaline basaltic magmas mixed with low-Al lamprophyric melts. This hypothesis is in conflict with N.V. Vladykin's concept that only one hypothetic magma existed and produced both the lamproites and the high-Al synnyrites. It was determined that the Al concentrations are correlated with those of Ba, Sr, and Ti, which makes it possible to relate Ba to high-Al and Ti and Sr to low-Al mixing melts.